Ketahanan Pangan Desa Kajarharjo Melalui Inovasi Pembuatan Nugget Daun Singkong dan Penggalakan Booster Organik Tanaman Guna Pertanian Sehat Berkelanjutan - Soekma Yeni Astuti; Elen Vera Indah Antika; Rifa Mareta Falaesa; Elmira Alya Kurniawan; Triya Anggun Prastika Sari; Afni Zannuba Nada Zakiyah; Andini Oktarina; Damai Rizky Desjuwarika Paulina; Dhanni Akbar Dharmawan; Esha Ayu Triana; M. Zenna Arta Caessar (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
Food security is a fundamental aspect of independent and sustainable village development. Kajarharjo Village has abundant natural resource potential, such as cassava and various herbal plants. However, the utilization of this potential is still less than optimal, both in terms of food processing and the implementation of environmentally friendly agriculture. This condition encourages the need for community service activities oriented towards food innovation and strengthening sustainable agriculture. This service activity was carried out using a participatory and applied approach at the Kajarharjo Village Hall. The main target is the village community, especially housewives and farmers. The program is implemented through two main activities, namely: (1) training in making cassava leaf nuggets as a nutritious food, an alternative local product, and a household business opportunity; and (2) training in making organic boosters from natural ingredients as a more environmentally friendly substitute for chemical fertilizers. Implementation methods include counseling, demonstrations, direct practice, and interactive discussions to ensure active community involvement. The results of the activities show an increase in community knowledge and skills. Housewives are able to process cassava leaves into products with nutritional and economic value, while farmers gain skills in mixing organic boosters that can improve soil quality and agricultural yields without relying on chemical fertilizers. The participants' enthusiasm was also evident in their active participation in the practical exercises and their desire to apply the knowledge gained in their daily activities. In conclusion, this activity successfully encouraged the utilization of local potential in Kajarharjo Village through food innovation and organic farming. Empowering the community through cassava leaf processing and organic fertilizer production not only strengthens food security but also opens up business opportunities, maintains environmental health, and supports the development of an independent, healthy, and sustainable village.